NDDVD: an integrated and manually curated Neurodegenerative Diseases Variation Database. (5th March 2018) - Yang, Yang; Xu, Chen; Liu, Xingyun; Xu, Chao; Zhang, Yuanyuan; Shen, Li; Vihinen, Mauno; Shen, Bairong
Abstract: Neurodegenerative diseases (NDDs) are associated with genetic variations including point substitutions, copy number alterations, insertions and deletions. At present, a few genetic variation repositories for some individual NDDs have been created, however, these databases are needed to be integrated and expanded to all the NDDs for systems biological investigation. We here build a relational database termed as NDDVD to integrate all the variations of NDDs using Leiden Open Variation Database (LOVD) platform. The items in the NDDVD are collected manually from PubMed or extracted from the existed variation databases. The cross-disease database includes over 6374 genetic variations of 289 genes associated with 37 different NDDs. The patterns, conservations and biological functions for variations in different NDDs are statistically compared and a user-friendly interface is provided for NDDVD at: http://bioinf.suda.edu.cn/NDDvarbase/LOVDv.3.0 . URL : http://bioinf.suda.edu.cn/NDDvarbase/LOVDv.3.0